2009
DOI: 10.1007/s00122-009-1221-0
|View full text |Cite
|
Sign up to set email alerts
|

Extent and structure of linkage disequilibrium in canola quality winter rapeseed (Brassica napus L.)

Abstract: Linkage disequilibrium was investigated in canola quality winter rapeseed to analyze (1) the prospects for whole-genome association analyses and (2) the impact of the recent breeding history of rapeseed on linkage disequilibrium. A total of 845 mapped AFLP markers with allele frequencies ≥0.1 were used for the analysis of linkage disequilibrium in a population of 85 canola quality winter rapeseed genotypes. A low overall level of linkage disequilibrium was found with a mean r2 of only 0.027 over all 356,590 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 38 publications
7
69
1
4
Order By: Relevance
“…Half of these displayed the same multilocus genotype as did Darmor-bzh or Yudal, while the other half was recombinant in the interval with alleles at the peak of the QTL being in agreement with the meiotic phenotype (see Supplemental Figure 3 online). These results confirm the most likely position for PrBn (between markers CB10013a and BnGMs185; Figure 3); owing to the rapid decay of linkage disequilibrium with distance in B. napus (Ecke et al, 2010), the statistical associations we found certainly reflects the close proximity of PrBn to the markers we used. These results also demonstrate that natural variation in meiotic behavior among B. napus allohaploids is consistent with the segregation of two alleles at the PrBn locus.…”
Section: Discussionsupporting
confidence: 82%
“…Half of these displayed the same multilocus genotype as did Darmor-bzh or Yudal, while the other half was recombinant in the interval with alleles at the peak of the QTL being in agreement with the meiotic phenotype (see Supplemental Figure 3 online). These results confirm the most likely position for PrBn (between markers CB10013a and BnGMs185; Figure 3); owing to the rapid decay of linkage disequilibrium with distance in B. napus (Ecke et al, 2010), the statistical associations we found certainly reflects the close proximity of PrBn to the markers we used. These results also demonstrate that natural variation in meiotic behavior among B. napus allohaploids is consistent with the segregation of two alleles at the PrBn locus.…”
Section: Discussionsupporting
confidence: 82%
“…The lower marker number on the BC 1 map is a consequence of the dominant inheritance of the AFLP markers used for marker analysis, which allowed only the mapping of markers with the 2) as the expected ratio *, **, *** diploidization rate is significantly different from the mean diploidization rate of 'Express 617' at P = 0.05 (v 2 = 3.84), P = 0.01 (v 2 = 6.64) and P = 0.001 (v 2 = 10.83), respectively, n.s. : not significant (P [ 0.05 or the diploidization rate is between the boundaries of the confidence interval of the mean of 'Express 617') in other maps, for example the map published by Ecke et al (2010), C4 (N14) was much larger. In addition, in the haploid MDE map and the BC 1 map-both maps developed in mapping populations derived from the same F 1 plant as the diploid MDE population-C4 was also only present as a small fragment or missing altogether.…”
Section: Discussionmentioning
confidence: 86%
“…AFLP analyses were carried out following the multiplexing protocol described by Ecke et al (2010). The same five primer sets (20 primer combinations) used in the development of the DH, haploid MDE and BC 1 maps and for the characterization of the ISLs were again used for the analysis of skewed segregations and for map construction in the diploid MDE population.…”
Section: Analysis Of Ploidy Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted from the frozen plantlets using the innuSPEED Plant DNA kit (Analytik Jena AG, Konrad-Zuse-Strasse 1, Jena, Germany) according to the manufacturer's instructions. AFLP analyses were carried out following the multiplexing protocol described by Ecke et al (2010). The same five primer sets (20 primer combinations) used in the development of the DH map, the maps of the two MDE and the BC 1 populations, as well as in the characterization of the ISLs were again used for AFLP analysis in the DEPC population.…”
Section: Donor Plant Growthmentioning
confidence: 99%